IMPLEMENTATION OF THINK PAIR SHARE (TPS) TO IMPROVE STUDENT’S LEARNING ACTIVENESS IN TEACHING WRITING AT THE SECOND GRADE OF SMAN 1 KURIPAN - Muhamad Suhaili (Sinar Lima, 2024)
This research was conducted based on the researcher's observations.The aim of this research is to describe and find out how think pair share is implemented to increase student learning activities in students' writing skills, increase student activity, student responses, student learning outcomes and describe the obstacles that occur during the learning process using Think Pair Share. Pair Share (TPS) Learning. TPS is designed to increase students' sense of responsibility towards the lesson itself and others. The type of research carried out in this research is a pre-experimental design using a